2016
DOI: 10.1016/j.rppnen.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

COPD patients with severe diffusion defect in carbon monoxide diffusing capacity predict a better outcome for pulmonary rehabilitation

Abstract: Pulmonary rehabilitation improves oxygenation, severity of dyspnea, exercise capacity and quality of life independent of level of carbon monoxide diffusion capacity in patents with COPD. Furthermore pulmonary rehabilitation may improve Dl values in COPD patients with severe diffusion defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
3
12
1
Order By: Relevance
“…It is shown that COPD patients with severe diffusing defect improved in Dl CO ( P = .04) value and FEV 1 % ( P = .01) value after PR. COPD patients with low diffusing capacity significantly higher changes in FEV1 and TLCO levels compared to those having moderate diffusing capacity . In our study the increase in FEV1% observed in both groups were statistically significant.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is shown that COPD patients with severe diffusing defect improved in Dl CO ( P = .04) value and FEV 1 % ( P = .01) value after PR. COPD patients with low diffusing capacity significantly higher changes in FEV1 and TLCO levels compared to those having moderate diffusing capacity . In our study the increase in FEV1% observed in both groups were statistically significant.…”
Section: Discussionsupporting
confidence: 53%
“…The patients with COPD had benefited from PR regardless of disease severity . Sometimes severe‐very severe COPD patients may benefit from PR more than mild‐moderate COPD patients . Our objective was COPD patients with LTOT benefit from PR as well as severe COPD patients without respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…No changes in D LCO have been shown by Mota et al [12], but apart from expiratory muscle training, no other rehabilitative respiratory intervention was administered to the patients enrolled in the study. However, the possibility of an increase in D LCO has been described in a recent paper by Sahin et al [13], which found that patients with a severe reduction in D LCO had better improvements in dyspnea compared to patients with a mild-moderate D LCO impairment due to blood flow redistribution to lung capillaries. We think that the latter hypothesis might be unlikely to occur because the redistribution of blood during exercise is temporary in nature, and, taking into account the need for an intact pulmonary peripheral vascular bed and the regional inhomogeneity of the D LCO raise during exercise in patients with COPD, unless the lung function test has been performed during or right after the exercise training, the explanation must be different.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent report described a significant increase in D LCO in severe patients with COPD after an 8-week outpatient PR program. Also in this case, the primary outcome was not D LCO , no subcomponents were measured, and the patients enrolled were 36 [13]. As opposed to heart failure [14], in COPD the KCO is related to the integrity of the alveolar-capillary membrane, and therefore to the extent of emphysema [15], which should constitute an irreversible phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…It measures the capacity of pulmonary alveolar and capillary surfaces for gas exchange (2). DL CO has been used in diagnosing and determining the severity of multiple lung diseases (1), as well as in determining their prognosis (3) and predicting their response to treatment (4,5). DL CO is frequently abnormal in chronic obstructive pulmonary disease (COPD) and is associated with emphysema measured from computed tomography (6) as well as with pulmonary vascular disease.…”
mentioning
confidence: 99%